Macroprudential Policy Study: Loan to Value Ratio in Home Ownership Credit Control - Muthia, Azka (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2019)
Housing credit in Indonesia has high growth from 2011. This growth could become excessive growth and cause housing bubble. Therefore, the government implement Loan To Value (LTV) to control mortgages. However, growth of housing credit is still fluctuating and slowing down when the government loosening LTV policy. This condition become the reasons to evaluate the success of LTV in Indonesia. The results using Hodrick Prescott (HP) filter method identified that housing credit several times experienced excessive growth and with Generalized Linear Autoregressive Moving Average (GLARMA) method shows that housing credit to GDP ratio is influenced by previous month and not influenced by LTV policy. Based on these results, Bank Indonesia can combine LTV policy with Debt To Income policy and determine the target of mortgage growth target to succesful housing credit control. Keywords: KPR; LTV; Excessive Growth; HP filter; GLARMA.JEL: C01; E52